Communication with resource-constrained devices through MQTT for control education. Issue 6 (2016) - Prada, Miguel A.; Reguera, Perfecto; Alonso, Serafín; Morán, Antonio; Fuertes, Juan J.; Domínguez, Manuel
Abstract: The developments on machine-to-machine systems are interesting for control education, not only for the opportunities to apply control and automation solutions to new problems, but also for the availability of new hardware, software and communication platforms. These technologies facilitate a low-cost and easier integration of physical equipment in educational tools such as the remote laboratories. This paper proposes the use of a lightweight protocol for communication with resource-constrained devices, MQTT, as an aid to integrate new devices in educational applications, specifically in those that use web standards such as Javascript to provide interactive user interfaces. To evaluate this approach, an educational application focused on the control of a DC motor position loop, built with EjsS, was developed. This tool uses the MQTT protocol to parametrize and communicate with an Arduino microcontroller that, in turn, controls a physical setup implemented with the Feedback MS150 modular system. The proposed approach enables the easy connection of interactive educational tools to new real equipment, especially those driven by resource-constrained devices.